Konsep Kemiskinan dalam Pandangan Hadis - La Adu; Arifuddin Ahmad; Erwin Hafis (Jurnal Ilmu Sosial dan Humaniora, 2023)
The author is interested in examining and explaining the issue of poverty from the perspective of Hadith of the Prophet Muhammad (peace be upon him), stating that poverty is caused by several factors, such as natural disasters, structured systems, exploitation of humans and nature, and political and economic systems. Poverty is a true reflection of social life, both in rural and urban areas, and even in developing countries, the issue of poverty cannot be overlooked. There is no guarantee that modernism will bring prosperity, as it depends on the aforementioned factors. In the hadiths that generally address poverty, it refers to those who have nothing, both materially and non-materially. Therefore, Islam is present as an oasis and a solution to the problems faced by humanity, especially for Muslims, by instructing its followers to pay zakat (charity) or infaq